Multicultural Education Approach by Religion Teacher at SMP Negeri 2 Ngemplak - Fadholi, Muhammad Irfan (Proceeding International Conference on Religion, Science and Education, 2022)
Multicultural Education Approach by Religion Teacher at SMP Negeri 2 Ngemplak. The background of the research is that students at State school 2 Ngemplak have diversity in terms of religion. There are religions in SMPN 2 Ngemplak, Islam, Christianity, Catholicism, and Hinduism. Creates a good harmony between students and the school community, making this school an adiwyata school. This study aims to 1) find out the implementation of the multicultural education approach by James Bank, 2) find out the results of the implementation of the multicultural approach, 3) find out the obstacles in implementing the multicultural education approach. This type of research is qualitative by using data collection techniques, namely through observation, interviews, and documentation. Data analysis techniques are data reduction by collecting data according to the research focus, displaying data in the form of narratives. The study results show that SMP N 2 Ngemplak has implemented four multicultural approaches, and the most dominant approach is social action. Second, the multicultural education approach results are divided into 3, namely results for schools for teachers and students. Third, there are obstacles in the multicultural education approach divided into three: Constraints originating from the school. Facilities for the teaching and learning process are still lacking, such as a particular room for each religion and each student's holy book according to his religion. In addition, the media about multiculturalism is also lacking. Constraints stemming from the teacher's lack of understanding of the culture of each religion and have not implemented a transformation approach so that multicultural education at SMP N 2 Ngemplak is less than optimal.